Milk drinking patterns among Malaysian urban children of different household income status - Khor, Geok Lin; Mohd Shariff, Zalilah; Sariman, Sarina; Huang, Mary Soo Lee; Mohamad, Maznorila; Chan, Yoke Mun; Chin, Yit Siew; Mohd Yusof, Barakatun Nisak (Annex Publishers, 2015)
Introduction: Good oral hygiene protects against oral diseases such as caries and gum infections. Twice daily tooth brushing with fluoride pastes and flossing are recommended to keep mouth clean and reduce plaque bacterial growth. Poor access to oral cleaning material and dental care services expose children from poor backgrounds to oral diseases. Background: Milk consumption is popular in Malaysia especially among the younger ages. Nonetheless, there is a lack of quantitative data on milk consumption by children in Malaysia. Methods: A cross-sectional study was undertaken on a sample of 749 children aged 1-10 years in the metropolitan areas of Kuala Lumpur. Approximately similar proportions of children were selected from low, middle and high household income categories. Socioeconomic background, dietary intake based on 24-hour recall and food records, were obtained for each child. Results: Prevalence of milk drinking was highest among aged 1-3 years (90.6%) followed by 86.1% aged 4-6 years, and 73.7% among ages 7-10 years. The youngest age group consumed averagely 3.5 (3.1 – 3.8) cups (200ml/cup) of milk daily, exceeding the recommendation of 2-3 cups a day by the Ministry of Health, Malaysia. There were no significant differences in the mean amounts of milk consumed among ages 1-3 years from low to high income categories. Children aged 4-6 years consumed, on average, 2.2 (1.9 – 2.4) cups/day, which is within the MOH recommendation, while that for ages 7-10 years, at 1.07 (0.9–1.2) cups/day, is below the recommendation. Conclusion: Parents of young children should be advised on the nutritional importance of providing foods from a variety of sources, so that the children obtain the right balance and mix of nutrients for optimum growth.